Aid measures for the unemployed and their assessment (in the light of the research results) = Działania pomocowe bezrobotnym i ich ocena (w świetle wyników badań) - Stankiewicz, Janina; Bortnowska, Hanna (Zielona Góra: Faculty of Economics and Management Press)
The negative consequences of the economic downturn started in 2008 in the USA affected many countries, including - Poland. In many organizations, it was necessary to carry out the redundancies, and these ones, if they were implemented in an unethical way, usually intensified dysfunctional processes within the companies.
Keywords: spowolnienie gospodarcze; zwolnienia pracownicze; outplacement; economic downturn; redundancies